Three ṭalaqs in one session from the perspective of maqaṣid al-sharīah - Asar, A. K. (Universiti Malaysia Pahang, 2022)
There is no consensus among Muslim jurists regarding the pronouncement of three ṭalāqs in one session: Does it constitute as one or three ṭalāqs? In Malaysia, a judge of Islāmic Court normally will give the final decision based on what most muftis hold in conforming the three ṭalāqs in one session. This opinion is based on the ijtihādic view of khalifaћ ‘Umar al-Khaṭṭāb when he saw many Muslims at his time have begun to hasten in the divorce. Researcher found that the ruling of three ṭalāqs in one session should constitute as one ṭalāq for normal cases nowadays. This ruling is stronger due to the practice of the Prophet himself when he allowed Rukānaћ to go back to his wife after the three ṭalaqs in one session. Its one of the Islāmic approaches to make the divorce three times and not once, as it gives the husband opportunity to review thoroughly, and this is his right. The ruling is line with the demand of Maqāṣid al-Sharī‘aћ in protecting lineage. However, for certain situations, the pronouncement of three ṭalāqs in one session may constitute as three ṭalāqs, this means that both ijtihād are correct based on spesific situations.